Karakter Morfologi dan Kimia 18 Kultivar Pamelo (Citrus maxima (Burm.) Merr.) Berbiji dan Tanpa Biji - Slamet Susanto; Arifah Rahayu; Dewi Sukma; Iswari S. Dewi (Institut Pertanian Bogor, 2011)
Pamelo is one of the oranges species which have variety of form, size, colour and taste. Most of the pamelo cultivars with seeds, while part of it is seedless. The concumen prefer to chose seedles than with seed because they could consume more. The research proposed to know the morphologycal and chemical characteristics of pamelo with seed and seedless. Characteristication done in RGCI and port harvesting laboratory at IPB to the Pamelo come from Sumedang, Pati, Kudus, Magetan, Aceh and Pangkep (South Sulaewsi) in the period of April 2009 until July 2010. The result of research shown that several pamelo seedless cultivars have pyriform, while other with seed have spheroid form. A few fruit from pamelo seedless cultivars have sweet taste until less taste, with pH of its juice vary from 6.2-6.3, except Jawa cultivar which have pH 4 which its total tertiration acid is 0.47- 0.50 g/g, PTT 9.8- 11.0 ( 0brix), PTT/ATT 19,5-25,3. Vitamine C content 38-48.2 mg/100 g and narigin content from 118,3-1063,2 mg/ml, while pamelo with seed have taste sweet acid, with fruit juice pH 3.7 - 4.7, except